2001
DOI: 10.1046/j.1365-2141.2001.02869.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heparin–platelet factor 4–IgG antibodies improves diagnosis of heparin‐induced thrombocytopenia

Abstract: Only a few patients with heparin‐induced antibodies develop heparin‐induced thrombocytopenia (HIT). In this study, we investigated whether different immunglobulin classes can be used to differentiate between antibody‐positive patients with and without HIT. Four different patient populations were investigated: 32 patients with the immune type of HIT with thromboembolic complications, 13 patients with HIT without thromboembolism, 24 patients with heparin–platelet factor 4 (PF4) antibodies without clinical sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 17 publications
5
59
0
1
Order By: Relevance
“…In that respect, it is both highly sensitive [37] and specific, because positive reactions are extremely rare in patients not exposed to heparin [30]. In various studies, 2-13% of patients thought to have HIT on clinical grounds were antibody-negative [40][41][42][43], but it is impossible to know how many of them may have had some other cause for their thrombocytopenia. In our experience, it is extremely rare for patients with ''typical'' HIT, especially those with associated thromboses, not to test positive in the ELISA.…”
Section: Solid-phase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In that respect, it is both highly sensitive [37] and specific, because positive reactions are extremely rare in patients not exposed to heparin [30]. In various studies, 2-13% of patients thought to have HIT on clinical grounds were antibody-negative [40][41][42][43], but it is impossible to know how many of them may have had some other cause for their thrombocytopenia. In our experience, it is extremely rare for patients with ''typical'' HIT, especially those with associated thromboses, not to test positive in the ELISA.…”
Section: Solid-phase Assaysmentioning
confidence: 99%
“…Although antibodies of the IgM and IgA classes are common in HIT [44,70], they are incapable of activating platelets through their Fc receptors, and it has been suggested that only IgG antibodies are ''clinically significant'' [6,42]. However, available commercial kits are designed to detect antibodies of all Ig classes, in part because of early reports describing patients with HIT (some with thrombosis) whose antibodies were exclusively IgM [70,71].…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…This end point was chosen because IgG class antibodies are more likely to cause HIT than antibodies of other classes. 21 All other end points were secondary end points.…”
Section: Interpretation Of Antibody Studiesmentioning
confidence: 99%
“…20 Further, clinical HIT is most likely to be caused by antibodies of IgG class. 21 Danaparoid sodium was obtained from Organon (Toronto, ON, Canada).…”
Section: Cross-reactivity Of Antibodies For Pf4/polysaccharide Complexesmentioning
confidence: 99%
“…To aid in the interpretation of a positive EIA, the clinician should consider the clinical scenario (i.e., the pretest probability based on the ''4Ts'') and the absolute value of the OD. Several studies have documented that high OD values (corresponding to high titers of HIT antibodies) are associated with a higher likelihood of a positive HIPA, a higher ''4Ts'' score (clinical HIT), and a higher probability of thrombotic complications [31][32][33][34][35].…”
Section: Laboratory Detection Of Hit Antibodiesmentioning
confidence: 99%